Microenvironmental Regulation of Long Noncoding RNA LINC01133 Promotes Cancer Stem Cell‐Like Phenotypic Traits in Triple‐Negative Breast Cancers. (26th August 2019) - Tu, Zhenbo; Schmöllerl, Johannes; Cuiffo, Benjamin G.; Karnoub, Antoine E.
Abstract: The fibrotic tumor microenvironment is a critical player in the pathogenesis of triple‐negative breast cancers (TNBCs), with the presence of fibroblastic infiltrates particularly correlating with tumors that are clinically advanced. On this front, we previously demonstrated that TNBCs are highly enriched in fibroblastic stromal progenitor cells called mesenchymal stem/stromal cells (MSCs) and that such cells play critical roles in promoting TNBC initiation and progression. How TNBC cells respond to MSC stimulation, however, is not fully understood, and stands to reveal contextual signals used by TNBC cells during tumor development and provide biomarkers and therapeutic targets of pertinence to TNBC management. Here, we report that MSCs strongly induced the long noncoding RNA (lncRNA) LINC01133 in neighboring TNBC cells. Indeed, although lncRNAs have been tightly associated with cancer development, their contributions to breast cancer in general, and to TNBC pathogenesis in particular, have not been fully elucidated, and we set out to determine if LINC01133 regulated malignant traits in TNBC cells. We establish that LINC01133 is sufficient, on its own, in promoting phenotypic and growth characteristics of cancer stem cell‐like cells, and that it is a direct mediator of the MSC‐triggered miR‐199a‐FOXP2 pathway in TNBC models. Furthermore, we show that LINC01133 is a critical regulator of the pluripotency‐determining gene Kruppel‐Like Factor 4 (KLF4), and that it represents a biomarker and prognosticator of disease outcome in the clinic. Collectively, our findings introduce LINC01133 as a novel functional driver of malignancy and a potential theranostic in TNBC.Stem Cells 2019;37:1281–1292 Abstract : LINC01133 responds to mesenchymal stem/stromal cell‐regulated miR‐199a/214‐FOXP2 pathway and upregulates the expression of the pluripotency master regulator KLF4 to drive cancer‐stem‐cell‐like phenotypic traits.